2015
DOI: 10.1063/1.4933126
|View full text |Cite
|
Sign up to set email alerts
|

Guiding and focusing of fast electron beams produced by ultra-intense laser pulse using a double cone funnel target

Abstract: A novel double cone funnel target design aiming at efficiently guiding and focusing fast electron beams produced in high intensity (>1019 W/cm2) laser-solid interactions is investigated via two-dimensional particle-in-cell simulations. The forward-going fast electron beams are shown to be directed and focused to a smaller size in comparison with the incident laser spot size. This plasma funnel attached on the cone target guides and focuses electrons in a manner akin to the control of liquid by a plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Simultaneously, the QMF increases to very high levels with time, effectively working to confine the fast electrons, figure 3(d). The QMF inside the cone gaps and beam collimator at t=1000 fs increases very rapidly to large value, ≈216 MG [21] for the type II. This is because that in the cone gaps and beam collimator with HDL there appear FEC density gradients and temperature gradients close to tip of the cone and on the contact layers of high and low density, which causes an increasing QMF, refer to [21] is the magnetic field, j h is the current density of fast electron.…”
Section: Qmfs With Beam Collimator and Hdlmentioning
confidence: 96%
See 1 more Smart Citation
“…Simultaneously, the QMF increases to very high levels with time, effectively working to confine the fast electrons, figure 3(d). The QMF inside the cone gaps and beam collimator at t=1000 fs increases very rapidly to large value, ≈216 MG [21] for the type II. This is because that in the cone gaps and beam collimator with HDL there appear FEC density gradients and temperature gradients close to tip of the cone and on the contact layers of high and low density, which causes an increasing QMF, refer to [21] is the magnetic field, j h is the current density of fast electron.…”
Section: Qmfs With Beam Collimator and Hdlmentioning
confidence: 96%
“…We can obtain the surface magnetic field by using a simple one-dimensional model, i.e., only considering the transverse variations. In fact, the magnetic flux acrossing the surface of density jump in different materials in the cone and beam collimator [21] where B 0 denotes the magnetic field amplitude at the contact layers in the target. Subscripts 1 and 2 are for the high and low density layers, respectively, and…”
Section: Qmfs With Beam Collimator and Hdlmentioning
confidence: 99%
“…Note that n 1 n 2 , d 1 δ pe1 and d δ pe2 in the nanolayered target. In order to get the values of B 0 and B 1 , we integrate Equation (4) across the interfaces of y = −d and y = d. Then, we can obtain the integrated magnetic flux [30,31]…”
Section: Generation Mechanism Of the Magnetic Fieldmentioning
confidence: 99%
“…This mechanism has a promising application because of the lower resistivity in the low-density plasma channel. However, it is also shown that the fast electrons are accumulated or deflected near the region of laser-plasma interactions by the magnetic field induced by the two stream instability (TSI) [35,36].…”
Section: Introductionmentioning
confidence: 99%